Opioid Receptors in Immune and Glial Cells—Implications for Pain Control - Machelska, Halina; Celik, Melih Ö. (Frontiers in Immunology, 2020)
Opioid receptors comprise μ (MOP), δ (DOP), κ (KOP) and nociceptin/orphanin FQ (NOP) receptors. Opioids are agonists of MOP, DOP and KOP receptors, whereas nociceptin/orphanin FQ (N/OFQ) is an agonist of NOP receptors. Activation of all four opioid receptors in neurons can induce analgesia in animal models, but the most clinically relevant are MOP receptor agonists (e.g., morphine, fentanyl). Opioids can also affect the function of immune cells, and their actions in relation to immunosuppression and infections have been widely discussed. Here, we analyze the expression and the role of opioid receptors in peripheral immune cells and glia in the modulation of pain. All four opioid receptors have been identified at the mRNA and protein levels in immune cells (lymphocytes, granulocytes, monocytes, macrophages) in humans, rhesus monkeys, rats or mice. Activation of leukocyte MOP, DOP and KOP receptors was recently reported to attenuate pain after nerve injury in mice. This involved intracellular Ca2+-regulated release of opioid peptides from immune cells, which subsequently activated MOP, DOP and KOP receptors on peripheral neurons. There is no evidence of pain modulation by leukocyte NOP receptors. More good quality studies are needed to verify the presence of DOP, KOP and NOP receptors in native glia. Although still questioned, MOP receptors might be expressed in brain or spinal cord microglia and astrocytes in humans, mice and rats. Morphine acting at spinal cord microglia is often reported to induce hyperalgesia in rodents. However, most studies used animals without pathological pain and/or unconventional paradigms (e.g., high or ultra-low doses, pain assessment late after discontinuation of chronic morphine treatment). Therefore, the opioid-induced hyperalgesia can be viewed in the context of addiction/withdrawal rather than pain management, in line with clinical reports. There is convincing evidence of analgesic effects mediated by immune cell-derived opioid peptides in animal models and in humans. Together, MOP, DOP and KOP receptors, and opioid peptides in immune cells can ameliorate pathological pain. The relevance of NOP receptors and N/OFQ in leukocytes, and of all opioid receptors, opioid peptides and N/OFQ in native glia for pain control is yet to be clarified.